MOTIF YANG BERPENGARUH PADA PROSES KEJIWAAN TOKOH SAM DALAM NOVEL SEBENING SYAHADAT KARYA DIVA SR - Dandy Ashghor Dawudi; Kamidjan Kamidjan; Agus Sulton (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research takes the object of Sebening Syahadat by Diva SR, this work is a novel that tells the story of the journey ofa teenager named Sam who is in the process ofsearching for identity. The journey is filled with interesting twits and turns embelissed with a love story that is very suitable if consumed by the younger generation who are learning to find identit. This study aims to reveal the value motives that led Sam’s character in finding his identity, which expected to be a material for reflection for readers, especially young people who are in the process of discovering his identity, the scope of the problem in this study is to reveal the value motives that affect the character’s psyche. Sam is told to have a rascal character.The research method used in this study took a descriptive qualitative approach, data colletion used was a literature study technique with stages of reading, note taking, coding for futher analysis. The analysis technique used is qualitative descriptive analysis technique.The result of the research in this research process indicate that the mental process of Sam’s character influenced by several factors, including: a. Motives in cultural factors (Situasional Factors), b. The motive for love begins with admiration for the attitude of someone who is full of noble values of character, c. The motive of curiosity and fulfillment of his needs for true value.